(untitled) (Indonesian Theological Justice Review, 2025)
Zakat, one of the five pillars of Islam, is a central practice of charity aimed at alleviating poverty and addressing social inequality. This paper examines how the Islamic practice of zakat contributes to economic justice in Indonesia, exploring its role in addressing poverty, reducing inequality, and promoting social welfare. The study provides an analysis of zakat as both a religious obligation and a tool for economic redistribution. The paper explores the ways in which zakat has been institutionalized in Indonesia through both formal channels (such as government-supported zakat organizations) and informal community-based efforts. It also evaluates the effectiveness of zakat programs in improving the economic conditions of the poor, examining both successes and challenges in implementation. Drawing from Islamic economic principles, the research highlights the moral and ethical imperatives of zakat in fostering a just and equitable society. The paper concludes by offering recommendations for optimizing the zakat system, including greater transparency, improved outreach to marginalized communities, and enhanced collaboration between religious institutions, the state, and civil society.